USING INORGANIC SAMPLE TO MAKE HANGING PLANT POT CRAFT IN GAMPONG BAGOK PANAH DUA - T. Edyansyah; Muhammad Roni; Amru Usman; Em Yusuf Iis; Rusydi Abubakar; Rico Nur Ilham (International Review of Practical Innovation, Technology and Green Energy (IRPITAGE), 2025)
This community service activity aims to address the problem of poorly managed inorganic waste in Bagok Panah Dua Village, Darul Aman District, East Aceh Regency. The local community, predominantly farmers, faces an increasing amount of waste that can negatively impact their health and the environment. One solution offered is to process inorganic waste, especially used bottles, into handicrafts in the form of hanging plant pots. Through training and mentoring, the community is provided with skills to recycle waste into products with economic value, while simultaneously raising awareness of the importance of waste management. This activity was carried out using an empowerment-based approach, where the community is invited to actively participate in sorting and recycling waste at the household level. The results of this activity demonstrated high enthusiasm from the community who successfully utilized used bottles to create marketable plant pots. In addition, this activity also succeeded in raising environmental awareness and having a positive impact on the community's economy. Despite several obstacles, such as a lack of additional resources to beautify the products, this activity still managed to provide significant benefits to the community of Bagok Panah Dua Village.